L’école dans la forêt. L’exemple d’un projet pédagogique porté par une attention à l’expérience des enfants - Julie Delalande (Recherches en Éducation)
What consequences does the practice of the outdoor school have on the school form? If the spatial and temporal context is in fact modified, the pedagogical practices and the relationships established with the children depend on the teachers' will. However, this desire remains constrained by an institutional context that is visible in particular in the formal curriculum. The research, carried out in a kindergarten practicing school in the forest one morning a week, shows how teachers deal with this curriculum and modify their relationships with the children. By being attentive to the child beyond the pupil and by valuing informal learning situations, they gather more spontaneous forms of oral expression than those instituted in the classroom.